Keparahan Penyakit Daun Keriting Kuning dan Pertumbuhan Populasi Kutukebul pada Beberapa Genotipe Cabai - Nissa Fawwaz Adilah; Sri Hendrastuti Hidayat (Jurnal Fitopatologi Indonesia, 2014)
Incidence of yellow leaf curl disease on chili pepper is very common in Indonesia and becomes major production constrain. The causal agent, Pepper yellow leaf curl virus (PYLCV), is only transmitted by insect vector, i.e. whitefly (Bemisia tabaci). Research was conducted to determine response of 6 chili pepper genotypes [Meteor, Rimbun, Tornado, F1(12X14), IPBC12, and 35C2] against infection of PYLCV and population growth of whitefly on each genotypes. Transmission of PYLCV to chili pepper genotypes was done using whitefly. Whitefly was maintained on each chili pepper genotypes to evaluate its population growth. Genotype IPBC12 was resistant to PYLCV having disease severity 0–9.2% and showed mild symptom. Genotypes Rimbun, Meteor, Tornado, F1(12X14), and 35C2 were susceptible having disease severity >20% and showed severe symptom. Resistance of IPBC12 might be correlated with the growth of whitefly on the genotype. The amount of whitefly eggs and its successful rate to become adult was relatively lower in IPBC12 than those in other genotypes. Genotype IPBC12 might be considered as resistance source in developing resistant variety of chili pepper to PYLCV.